2015
DOI: 10.1038/ni.3101
|View full text |Cite|
|
Sign up to set email alerts
|

The endothelial protein PLVAP in lymphatics controls the entry of lymphocytes and antigens into lymph nodes

Abstract: In the lymphatic sinuses of draining lymph nodes, soluble lymph-borne antigens enter the reticular conduits in a size-selective manner and lymphocytes transmigrate to the parenchyma. The molecular mechanisms that control these processes are unknown. Here we unexpectedly found that PLVAP, a prototypic endothelial protein of blood vessels, was synthesized in the sinus-lining lymphatic endothelial cells covering the distal conduits. In PLVAP-deficient mice, both small antigens and large antigens entered the condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
214
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(218 citation statements)
references
References 48 publications
2
214
1
1
Order By: Relevance
“…[20][21][22] Furthermore, it has been recently shown that PV1 is not only expressed on blood vessels but also on lymphatic endothelial cells where it forms a physical filter that modulates the passage of soluble antigens and the transmigration of lymphocytes. 23 Interestingly, we found that the expression of PV1 is up-regulated on blood capillaries upon infection with Salmonella typhimurium, an enteric pathogen known to disseminate systemically. 24 The increase in PV1 expression on ECs correlates also with Salmonella dissemination to systemic sites, with higher serum levels of alanine transaminases (ALT), used as indicators of liver damage, and with an increased extravasation of large molecules out of the intestinal capillaries indicating endothelial leakiness.…”
mentioning
confidence: 86%
“…[20][21][22] Furthermore, it has been recently shown that PV1 is not only expressed on blood vessels but also on lymphatic endothelial cells where it forms a physical filter that modulates the passage of soluble antigens and the transmigration of lymphocytes. 23 Interestingly, we found that the expression of PV1 is up-regulated on blood capillaries upon infection with Salmonella typhimurium, an enteric pathogen known to disseminate systemically. 24 The increase in PV1 expression on ECs correlates also with Salmonella dissemination to systemic sites, with higher serum levels of alanine transaminases (ALT), used as indicators of liver damage, and with an increased extravasation of large molecules out of the intestinal capillaries indicating endothelial leakiness.…”
mentioning
confidence: 86%
“…3C and Table S2). These cells, frequently named "sinus lining cells," extend their processes across the SCS to enwrap sinus traversing conduits, which constitute the initial part of the intricate conduit system branching within the LN cortex (14) (Fig. 3 C and D).…”
Section: Btv Infects Endothelial Cells and Macrophages In The Ln Sinumentioning
confidence: 99%
“…Intriguingly, diaphragms formed by lymph endothelial cells selectively regulate access of lymph-borne proteins, etc. into the conduits that permeate the cortex of the node (12). Very small particulates, soluble proteins and lymph fluid deposited in the SCS can enter the node's parenchyma through these conduits.…”
Section: Viral Trafficking To and Infection Of The Lymph Nodementioning
confidence: 99%
“…Medullary macrophages, heavily distributed in the medullary sinuses, are distinguished by the expression of F4/80 in addition to CD169. Because of their strategic locations in and adjacent to LN sinuses, these macrophages have direct access to incoming lymph fluid that cannot reach the B cell follicles or T cell zone due to size exclusion (12,19).…”
Section: Viral Trafficking To and Infection Of The Lymph Nodementioning
confidence: 99%
See 1 more Smart Citation